1993
DOI: 10.1111/j.1365-2621.1993.tb09342.x
|View full text |Cite
|
Sign up to set email alerts
|

Low‐dose Gamma Irradiation and Refrigerated FStorage in vacua Affect Microbial Flora of Fresh Pork

Abstract: Vacuum-packaged ground fresh pork samples absorbed gamma radiation doses of 0. 0.57. 1.91. 3.76. 5.52. or 7.25 kGv at 2°C. Samolcs were analyzed'after i, 7, i4, 2i, 28, 'or 35 days itorage at 2"C'for presence and number of aerobic and anaerobic mesophiles and endospore formers, and aerobic psychrotrophs. Conventional plate counts did not detect surviving microflora in any sample that received an absorbed dose of 1.91 kGy or higher, even after refrigerated storage for up to 35 days. The microflora in the contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 7 publications
0
16
0
Order By: Relevance
“…16 However, irradiation-induced chemical changes can lead to undesirable odour and colour changes in meat. 17 Since the colour of meat is an important parameter for consumer acceptability, proper measurement of colour is an important tool in muscle food research. Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…16 However, irradiation-induced chemical changes can lead to undesirable odour and colour changes in meat. 17 Since the colour of meat is an important parameter for consumer acceptability, proper measurement of colour is an important tool in muscle food research. Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Vibrio species have proven relatively sensitive to low dose of gamma irradiation processing compared with other pathogens (Bandekar et al, 1987). Gram-negative bacteria are more sensitive to irradiation than Gram-positives (Thayer, Boyd, & Jenkins, 1993). Several researchers have demonstrated that low dose irradiation, which could virtually eliminate.…”
Section: Tablementioning
confidence: 99%
“…2001). In addition, Gram‐negative bacteria are more sensitive to irradiation than Gram‐positives (Thayer et al. 1993).…”
Section: Resultsmentioning
confidence: 99%